Pengaruh Desain Bangunan Paramount Skyline Complex terhadap Aksesibilitas Driver Online ke Universitas Matana - Zenon Hassel Rilianto; Moses Luca Hariyanto (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2019)
Population growth in Indonesia makes the number of motorized vehicles increase rapidly making people increasingly lazy to use public transportation. But there are some people making online public transport applications such as online motorcycle taxi and online taxis. With the application, people are increasingly willing to use the application to increase people to use public transportation. Many who use the application are office workers and students. For paramount skyline complex buildings here make accessibility for the pickup area for online drivers. To determine circulation in the area of the Matana University. This study uses a quantitative method to determine that the presence or absence of these influences using SPSS version 16. Through this study, it is expected to provide knowledge about the influence of the paramount skyline complex building design on the accessibility of online drivers to matana universities. The results of this study indicate that in fact there is a strong and significant relationship with r = 0.776 and t = 8.520 between platform settings for the adaptability of KRL users. And the influence of platform settings on the adaptability of KRL users is 60.2%.